(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
Background: while breast feeding is a natural act, it is also a learned behavior. The right technique of feeding in the right position is the key to success of breastfeeding. Methods: to assess the feeding practice including positioning, attachment and suckling of under 6 months’ infants, a cross-sectional study was undertaken at R. G. Kar Medical College and Hospital, India, among 99 mothers in 2010. Results: 59.8% mothers completed feeding from one breast before going to the next breast. 77.3% mothers alternated their breasts during subsequent feeds. 41.2% babies were well attached, 47.4% babies were correctly positioned. Conclusions: there is a need to teach the mothers the techniques of correct positioning and attachment, especially, in the post natal period before discharge from the hospital after delivery.